KONSEP DOMINASI NAFSU TERHADAP AKAL DALAM AL-QUR’AN DITINJAU DARI PERSPEKTIF PENDIDIKAN ISLAM - Sitorus, Wildan; Sinaga, Ali Imran; Khairuddin, Khairuddin (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2024)
This research specifically aims at (1) To determine the relevance of reason and lust in education, (2) To determine the role of reason in lust, (3) To determine the dominance of lust over reason viewed from the perspective of Islamic education. This research uses a qualitative research method, library research. Library research is a series of activities carried out by a researcher with various forms of written work by collecting library data, carrying out reading activities, and then taking notes and then processing the research material that has been received. The results of this research show that (1) Reason and passion have relevance to Islamic Religious Education. The relevance of reason to Islamic religious education can be seen in the formulation of educational goals. Meanwhile, the relevance of lust to Islamic Religious Education can be seen when Islamic Religious Education plays a role in forming, directing and guiding lust towards goodness by providing and imparting moral and character education lessons. (2) Reason has a very important role in lust. First, reason acts as a tool that can differentiate between good and bad. Second, reason acts as a tool that can restrain, bind, direct and control human desires. (3) The dominance of lust over reason is seen when there is a battle between reason and lust in the human soul. The dominance of lust over reason occurs when the human nature of piety is defeated by the nature of honesty, so that this is what leads humans to commit evil and disobedience which has a detrimental impact and makes human life miserable.